2014
DOI: 10.1016/j.jpedsurg.2014.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of surgical burden associated with pediatric intestinal failure: A multicenter cohort analysis

Abstract: Background Pediatric intestinal failure (IF) patients require many surgical procedures over the course of their illness. The number and variety of surgical procedures, as well as patient characteristics associated with this burden of surgical procedures, remain largely unknown. Methods Data from a large, multicenter retrospective study of pediatric intestinal failure (PIFCON) were reviewed. Infants from 14 multidisciplinary IF programs were enrolled, with study entry defined as PN dependence for > 60 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…In this cohort, NEC is the most frequent cause of SBS, accounting for 34% of all cases, which is consistent with other reports regarding pediatric intestinal failure [15, 22]. Multivariable regression demonstrated that the diagnosis of NEC, in addition to other expected parameters including median serum citrulline concentration, absence of a stoma, and percent expected bowel length were associated with enteral autonomy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this cohort, NEC is the most frequent cause of SBS, accounting for 34% of all cases, which is consistent with other reports regarding pediatric intestinal failure [15, 22]. Multivariable regression demonstrated that the diagnosis of NEC, in addition to other expected parameters including median serum citrulline concentration, absence of a stoma, and percent expected bowel length were associated with enteral autonomy.…”
Section: Discussionsupporting
confidence: 90%
“…However, children who are unable to wean from PN have increased mortality and additional burdens, including risk of intestinal failure associated liver disease (IFALD), central line associated blood stream infections (CLABSI), and increased costs[6, 8, 15, 16]. An accurate understanding of the relationship between etiology of SBS and likelihood of weaning from PN may influence clinical management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short bowel syndrome is a common underlying diagnosis in the PN-dependent pediatric population that leads to the need for multiple invasive procedures and surgeries during childhood. A typical child with intestinal failure undergoes a median of four invasive abdominal procedures and highlights the importance of accurately defining the potential risk of FO-associated bleeding 11 . The goal of this report is to describe the incidence of clinically significant post-procedural bleeding (CSPPB) in pediatric patients receiving parenteral FO monotherapy for the treatment of IFALD.…”
Section: Introductionmentioning
confidence: 99%
“…SBS associated complications including intestinal failure associated liver disease (IFALD), small bowel bacterial overgrowth (SBBO), nephrocalcinosis, cholelithiasis, and metabolic bone disease (MBD) are quite prevalent in this patient population [5][6][7][8][9]. A high resource and disease burden is also reported in children with SBS after initial discharge and in younger children with SBS [10][11][12]. There is a paucity of data regarding burden of disease in adolescents with neonatal onset SBS and their ability to wean from PN.…”
mentioning
confidence: 99%